DEVELOPMENT OF AGRICULTURAL ECONOMY OF UZBEKISTAN (British Journal of Global Ecology and Sustainable Development, 2024)
The article on the formation of a class of owners in the countryside, the provision of economic freedoms to peasants shows broad opportunities for the development of legal, organizational, economic and technological foundations for the further development of the agricultural sector. The reform requires improving the mechanism for financing and lending to rural producers, developing market and rural infrastructure, and expanding the service sector. The agricultural production indicators achieved in recent years make it possible to ensure food security for the population, supply sufficient raw materials for local industry and increase the volume of agricultural exports, expanding their geography.